(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
One of the tourism destinations prioritized by the Indonesian government for development to promote environmental sustainability is the Borobudur tourist region. The concept of the designed approach aims to maximize social benefits and economic prosperity while minimizing the negative impacts of tourism on the environment. This study investigates the factors that contribute to local community support for the development of sustainable tourism activities in the Borobudur tourism region and explores the perceptions of the local population regarding the impacts of sustainable tourism. To facilitate this inquiry, a conceptual framework was devised. A survey was conducted among 100 participants, resulting in a 100% valid response rate. The PLS-SEM approach was employed for this evaluation. The findings demonstrate a beneficial correlation between social, economic, and health variables that affect the quality of life in adjacent towns. Additionally, this research showcases the local population’s favorable attitude towards the potential expansion of Borobudur tourism. The findings reveal significant academic and practical contributions to the expansion of sustainable community-based tourism in Central Java. Future development assistance for this sector must consider local culture and environmental preservation by engaging local communities in maintaining infrastructure and resolving social conflicts.